Microstructural and surface property variations due to the amorphous region formed by thermal annealing in Al-doped ZnO thin films grown on n-Si (100) substrates - Han, J. H.; No, Y. S.; Kim, T. W.; Lee, J. Y.; Kim, J. Y.; Choi, W. K. (ELSEVIER, 2010)
X-ray diffraction (XRD) patterns revealed that the as-grown and annealed Al-doped ZnO (AZO) films grown on the n-Si (1 0 0) substrates were polycrystalline. Transmission electron microscopy (TEM) images showed that bright-contrast regions existed in the grain boundary, and high-resolution TEM (HRTEM) images showed that the bright-contrast regions with an amorphous phase were embedded in the ZnO grains. While the surface roughness of the AZO film annealed at 800 degrees C became smoother, those of the AZO films annealed at 900 and 1000 degrees C became rougher. XRD patterns, TEM images, selected-area electron diffraction patterns, HRTEM images, and atomic force microscopy (AFM) images showed that the crystallinity in the AZO thin films grown on the n-Si (1 0 0) substrates was enhanced resulting from the release in the strain energy for the AZO thin films due to thermal annealing at 800 degrees C. XRD patterns and AFM images show that the crystallinity of the AZO thin films annealed at 1000 degrees C deteriorated due to the formation of the amorphous phase in the ZnO thin films. (C) 2009 Published by Elsevier B. V.